Phage Therapy in Prostatitis: Recent Prospects - Górski, Andrzej; Jończyk-Matysiak, Ewa; Łusiak-Szelachowska, Marzanna; Międzybrodzki, Ryszard; Weber-Dąbrowska, Beata; Borysowski, Jan; Letkiewicz, Sławomir; Bagińska, Natalia; Sfanos, Karen S. (Frontiers in Microbiology, 2018)
Prostatitis has various etiology including bacterial infection and dysregulated immunity; some of its forms remain a serious therapeutic challenge. Inflammation occurs in all forms of this disorder and is proposed to predispose to the development of prostate cancer. There are reports that phage therapy is effective in chronic bacterial prostatitis. Recent findings suggest that phages not only eliminate bacteria, but also mediate immunomodulating (for example anti-inflammatory) functions. The immunomodulating effects of phages could be beneficial in treating all forms of prostatitis and play some role in the prevention of the development of prostate cancer. As the etiological factors contributing to the majority of prostatitis cases remains largely unknown, and management options are often likewise limited, phage therapy merits further research as an attractive therapeutic option given its immunomodulating effects irrespective of the underlying causative factor(s).